Additively Produced Ti-6Al-4V Osteosynthesis Devices Meet the Requirements for Tensile Strength and Fatigue - Alisdair R. MacLeod; Matthew Bishop; Alberto Casonato Longo; Alborz Shokrani; Chris Rhys Bowen; Harinderjit Singh Gill (Journal of Manufacturing and Materials Processing, 2025)
The purpose of this study was to estimate the peak stresses in a laser powder bed fusion (LPBF) additive-manufactured (AM) osteosynthesis plate during physiological loading and establish if the mechanical properties of LPBF titanium alloy were suitable for this use case. Finite element models of subject-specific osteosynthesis plates for a cohort of 28 patients were created and used to calculate the peak maximum principal stresses during physiological loading, which was estimated to be 166 MPa twelve weeks post-operatively. All specimens were LPBF additively manufactured in Ti-6Al-4V alloy. ISO compliant tests were performed for tensile and fatigue, respectively. Fatigue testing was performed for specimens that had been heat-treated only and those that had been heat-treated and polished. The Upper Yield Stress was 1012.5 ± 19.2 MPa. The fatigue limit was 227 MPa for heat-treated only specimens and increased to 286 MPa for heat-treated and polished specimens. The finite element predicted stresses were below the experimentally established limits of yield and fatigue. The tensile and fatigue properties of heat-treated LPBF Ti-6Al-4V are therefore sufficient to meet the mechanical requirements of osteosynthesis plates. Polishing is recommended to improve fatigue resistance.